Знайдіть значення виразу (2b-6) (6b + 2) -6b (2b + 6) при b = 2 7

Знайдіть значення виразу (2b-6) (6b + 2) -6b (2b + 6) при b = 2 7

  • = 12b ^ 2 + 4b-36b-12-12b ^ 2-36b = -68b-12 = -68 * 2,7-12 = -195,6
  • (2 * 2,7) (6 * 2,7 + 2) -6 * 2,7 (2 * 2,7 + 6) = (5,4 * 18,2) - (16,2 * 11,4 ) = 98,28-184,68 = -86,4

Понравилась статья? Поделись с друзьями:
Добавить комментарий

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

+ 73 = 83